An analytical study of neuromuscular coupling at maximum load for weightlifters utilizing high-density electromyography of the surface for the snatch lift - Yasir, Omar Khalid (Journal of Physical Education, 2026)
this study aimed to analyze the characteristics of the neuromuscular coupling during maximal load performance (100% maximum performance of one-repetition) in the snatch lift among weightlifters, by using a high-density surface electromyography (HD-sEMG). The study adopted a descriptive analytical approach that have a correlational nature which included a sample of 12 weightlifters from the Al-Kadhimiya Sports Club with at least five years of training experience. The electrical activity (of the two main muscles involved in the second pull phase of the snatch lift, namely the vastus lateralis and the gluteus maximus), has been  recorded, along with the analysis of motor unit discharge rate and muscle fiber conduction velocity by using an advanced decomposition algorithms. The results showed a strong correlation between the maximum strength and the neural discharge rate in the vastus lateralis muscle, as well as a significant correlation between the fiber conduction velocity in the same muscle and maximum strength (1RM) in the snatch lift. In addition, a moderate correlation has been also observed between the discharge rate in the gluteus maximus muscle and maximum strength, but the conduction velocity in this muscle has not reached the level of statistical significance. However, the main conclusions that have been based on the study's results indicate that neural efficiency, (particularly the regulation of discharge rate with the recruitment of high-threshold motor units during the second pull phase of the snatch lift), represents a fundamental determinant of strength production under maximum loads.